2000
DOI: 10.1161/01.res.87.12.1157
|View full text |Cite
|
Sign up to set email alerts
|

Role of Structural Barriers in the Mechanism of Alternans-Induced Reentry

Abstract: Previously, using an animal model of T-wave alternans in structurally normal myocardium, we demonstrated that repolarization can alternate with opposite phase between neighboring myocytes (ie, discordant alternans), causing spatial dispersions of repolarization that form the substrate for functional block and reentrant ventricular fibrillation (VF). However, the mechanisms responsible for cellular discordant alternans and its electrocardiographic manifestation (ie, T-wave alternans) in patients with structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 54 publications
10
168
1
1
Order By: Relevance
“…Without control, this magnitude is largest in the state of discordant alternans shown in the top panel of Fig. 1(c), which is directly analogous to the state that has been shown to promote the initiation of high-frequency reentrant spiral waves in ventricular tissue [2][3][4][5]. In contrast, this magnitude is reduced in the standing wave mode induced by feedback control shown in the bottom panel of Fig.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Without control, this magnitude is largest in the state of discordant alternans shown in the top panel of Fig. 1(c), which is directly analogous to the state that has been shown to promote the initiation of high-frequency reentrant spiral waves in ventricular tissue [2][3][4][5]. In contrast, this magnitude is reduced in the standing wave mode induced by feedback control shown in the bottom panel of Fig.…”
mentioning
confidence: 77%
“…Because heart cells are refractory to further stimulation during an action potential, alternans of APD results in an alternans of refractoriness, the magnitude of which may vary across different regions of the heart. Several studies have shown that the resulting spatial dispersion of refractoriness facilitates the development of local conduction block [2][3][4][5], which may in turn cause the normally planar wave of electrical excitation in cardiac tissue to break and form spiral waves [6]. If the spiral waves also encounter regions of disparate refractoriness, they may disintegrate into multiple wavelets, which may account for the onset of the lethal heart rhythm disorder ventricular fibrillation [7][8][9].…”
mentioning
confidence: 99%
“…Dans un modèle expérimental de défaillance cardiaque induite par la stimulation rapide et prolongée des ventricules, l'augmentation de la pression auriculaire entraîne un taux important de mort cellulaire et le remplacement des myocytes nécrosés par du collagène, ce qui correspond à la fibrose [14]. Ce remodelage engendre l'isolation électrique des myocytes voisins et forme des barrières à la propagation propices au processus de réen-trée [15]. L'interaction onde-obstacle peut augmenter la courbure de l'onde électrique, ce qui ralentit sa propagation et module la durée du potentiel d'action [16,17].…”
Section: Microstructure Et Arythmies Auriculaires Arythmies Et Procesunclassified
“…8) Cell-to-cell uncoupling, caused by the insulating structural barriers seen in some types of heart diseases, augment the transmural gradients of action potential duration through inhibition of electrotonic influence from neighboring cells. 9) We speculated that granulomatous changes of the ventricles associated with lymphocyte infiltration or fibrosis, or both, would cause cell-to-cell uncoupling and increase the transmural gradient of action potential duration, which would result in the augmentation of MVTWA in patients with cardiac sarcoidosis. We therefore hypothesized that noninvasive examination of MVTWA allows prediction of cardiac involvement in patients with sarcoidosis.…”
Section: Sarcoidosis Is a Systemic Granulomatous Disorder Of Unknown mentioning
confidence: 99%